Is overall and timing-specific physical activity associated with depression in older adults? - Chen, Jiaren; Lai, Ting-Fu; Lin, Li-Jung; Park, Jong-Hwan; Liao, Yung (Frontiers in Public Health, 2023)
Objective Regarding the circadian rhythm regulating an individual’s response to external stimulation, it remains unclear whether older adults engaged in physical activity at different times of day may be differently related to depression symptoms. Thus, this study aimed to investigate the association between overall and timing-specific physical activity and depressive symptoms in older Taiwanese adults. Methods This cross-sectional study was conducted at a medical center in Taipei City, Taiwan, between September 2020 and December 2021. The participants were community-dwelling older adults aged ≥65 who could walk independently and were not at high risk of cognitive dysfunction. Physical activity was measured using a triaxial accelerometer (GT3X+, ActiGraph) and categorized into timing-specific periods (morning: 06:01–12:00; afternoon: 12:01–18:00; evening: 18:01–24:00) as well as overall physical activity, which included both light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA). A 15-item Geriatric Depression Scale was utilized to assess and measure depressive symptoms. Multivariate linear regression models were estimated for data analysis. Results A total of 180 older adults (55.0% female; 80.5 ± 7.1 years old; 18.3% at risk of depression) were included. On average, the participants spent 237.3 (± 85.7) minutes in LPA per day and 12.8 (± 17.0) minutes in MVPA per day. The results showed that overall MVPA engagement was associated with lower depressive-symptom scores [B = −1.357, 95% CI (−2.561, −0.153)] in older adults. However, no significant associations were observed between overall LPA, timing-specific MVPA and LPA, and depression in older adults. Conclusion To prevent depression in older adults, it is advisable to accumulate a higher amount of MVPA throughout the entire day rather than engage in LPA. Further studies employing a prospective design are necessary to validate and strengthen our findings.